VILLAGE EMPLOYEE STRATEGY TO IMPROVE YOUNG GENERATION PARTICIPATION IN DEVELOPMENT (Study in Surabaya Sub-District, Kedaton District City of Bandar Lampung) - fadilah h; eny inti suryani (DEMOKRASI, 2021)
The younger generation is the hope of the nation in the future. The participation of the younger generation in development today is not optimal. The aim of this study is to find out how the strategy implemented by kelurahan employees in increasing the participation of young people in development and this research is carried out using descriptive methods with qualitative approaches. . Based on the results of the study that the strategy of the Surabaya Kelurahan, Kedaton Bandar Lampung Subdistrict in increasing young people participation in development included: (1) The education and training held by the Surabaya District to increase the participation of the younger generation in development included training on the dangers of drug and alcohol use , improvement of Productive Economic Enterprises such as sewing training, training in making woven crafts, fisheries training, making paving blocks, making flower pots (2) Program for the implementation of empowerment of young people includes optimizing risma activities through teaching and learning activities for TPA children, facilitating MSMEs through economic empowerment productive, prevention of the growth of juvenile delinquency, drug and liquor abuse, opening a savings and loan cooperative for small business actors and holding sports competitions for the younger generation. (3) The implementation of entrepreneurial development for the young generation carried out in the field of training in making tempeh chips, bananas and crackers, lele fish and merang mushrooms, broiler chicken poultry cultivation and wood carving crafts get a positive response from the younger generation. Keywords: Village Employee, Strategy, Generation Participation